Modelling in economic evaluations of medicines - Lakić, Dragana; Stević, Ivana; Odalović, Marina; Tadić, Ivana (Archives of Pharmacy, 2021)
Economic evaluation in health (also known as pharmacoeconomic in case of medicines) identifies, measures, and values costs and outcomes of alternative healthcare technologies, and can be performed alongside controlled clinical trials, but analytical modelling is usually used. Decision trees and Markov models are the two most common approaches used in economic evaluation. The biggest advantages of a decision tree are clarity, simplicity, and straightforwardness. On the other hand, the main advantage of the Markov model is its ability to incorporate complex events into the simulation, which is practically impossible to do with a decision tree. Reimbursement policy in Serbia mandatorily incorporates economic evaluations to promote availability and accessibility of the prescription medicines. To show pharmacoeconomic value of a medicine, budget impact analysis and the cost-effectiveness analysis should be included. The latter should be conducted using appropriate modelling techniques. However, since no official methodological guidelines about the modelling and economic analysis exist, the submissions by marketing authorization holders vary greatly. The future of pharmacoeconomic modelling depends on the research area of interest, with new frameworks and approaches being developed.